Eksplorasi Penerimaan Aplikasi Pegadaian Digital Service (PDS) Melalui Model UTAUT3 dan Trust - Dessy Triana Putri; Dedy Setiawan; Dewi Lestari (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to evaluate the factors influencing user acceptance of the Pegadaian Digital Service (PDS) application by applying the UTAUT3 framework with the addition of the Trust variable. Based on interview findings and user review analysis, PDS adoption remains relatively low due to initial access difficulties, inconsistent navigation, and concerns regarding data security. The research employed a quantitative approach with 100 active PDS users as respondents. The collected data were analyzed using the SEM-PLS method. The results indicate that Effort Expectancy, Social Influence, and Personal Innovativeness significantly affect Behavioral Intention, while Habit has a significant effect on Use Behavior. In contrast, Performance Expectancy, Facilitating Conditions, Price Value, Trust, and Behavioral Intention do not significantly influence Use Behavior. The model demonstrates moderate explanatory power (R² = 0.555 for BI and 0.274 for UB). These findings suggest that, in collateral-based financial services such as PDS, behavioral intention alone is insufficient to drive actual usage without adequate supporting conditions. The practical implications highlight the importance of improving user experience, strengthening socially driven campaigns, and fostering user habits through digital incentives to enhance PDS adoption.